Factors that influence employees productivity in Kumpulan Wang Simpanan Pekerja (KWSP) Kangar, Perlis / Nurliana Fahanis Ismail - Ismail, Nurliana Fahanis (2016)
This study aims to analyse the factors that influence employees 'productivity in Kumpulan Wang Simpanan Pekerja (KWSP) Kangar, Perlis. Based on the literature discussed, the three factors considered as the important elements influence the employees' productivity that need to be investigated. The independent variables are media usage, trust and interpersonal relationships, while the dependent variable is employees' productivity. The research question lies in whether each of those factors has a simultaneous and partial effect on the employees' productivity or otherwise. Using the quantitative method, the population of this study was 100 respondents with N=70. The primary data gathered in the form of questionnaires with a Likert typed-scale were then analysed using the multiple regression method. According to the findings, only variable interpersonal relationship is significant with the employees' productivity and the other two variables which are media usage and trust are not significant with the employees' productivity